2024
DOI: 10.1097/corr.0000000000003040
|View full text |Cite
|
Sign up to set email alerts
|

High Area Deprivation Index is Associated With Not Achieving the Patient-acceptable Symptom State After TKA

Matthew J. Hadad,
Ignacio Pasqualini,
Alison K. Klika
et al.

Abstract: Background The Area Deprivation Index (ADI) approximates a patient’s relative socioeconomic deprivation. The ADI has been associated with increased healthcare use after TKA, but it is unknown whether there is an association with patient-reported outcome measures (PROMs). Given that a high proportion of patients are dissatisfied with their results after TKA, and the large number of these procedures performed, knowledge of factors associated with PROMs may indicate opportunities to provide support to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Although the work of Hadad et al [4] represents an important step in the journey to better understanding the many factors that affect our patients and procedures like TKA, there is much more to do. Since as many as 20% of our patients who undergo TKA aren't satisfied with the outcome, further research into the impact of the factors under our control and those outside of our control is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the work of Hadad et al [4] represents an important step in the journey to better understanding the many factors that affect our patients and procedures like TKA, there is much more to do. Since as many as 20% of our patients who undergo TKA aren't satisfied with the outcome, further research into the impact of the factors under our control and those outside of our control is needed.…”
mentioning
confidence: 99%
“…Published in this issue of Clinical Orthopaedic and Related Research ® , Hadad et al [4] studied a relatively large retrospective cohort of patients who underwent TKA within a tertiary health system in two states. The authors found that increased socioeconomic disadvantage as determined by the ADI was associated with not achieving the patient-acceptable symptom state (PASS) thresholds for the Knee Injury and Osteoarthritis Outcome Score (KOOS) Pain and KOOS JR. Interestingly, other PROMs and satisfaction were not associated ADI in the studied patient population.…”
mentioning
confidence: 99%